Longevidade da união de sistemas adesivos universais em dentina hígida e afetada - Follak, Andressa Cargnelutti (2016)
A new generation of adhesive systems are currently available on market. They were reported on the literature as universal adhesives or multimode adhesives . These adhesives are versatile, as they can be use in either etch-and-rinse or self-etch strategy. However, only a few data is available about long-term bonding behavior of universal adhesive systems. Then, the aim of this study is to evaluate immediate and six months bond strength of different universal adhesive systems on sound and caries-affected dentin, either on etch-and-rinse or self-etch strategies. The adhesive systems tested were: Scotchbond Universal (3M ESPE), All-Bond Universal (Bisco), Prime & Bond Elect (Denstply Caulk), Adper Single Bond 2 (3M ESPE) and Clearfil SE Bond (Kuraray Noritake Dental). All adhesive systems were applied under manufacturer s instructions and a composite block was build up on dentin surfaces. Caries-affected dentin was artificially induced by pH-cycling (8h immersed on demineralizing solution and 16h on remineralizing solution, for 14 days). Stick shaped specimens (0,8 mm²) were obtained to be submitted to microtensile test at immediate time or after 6 months of storage. Bond strength data (MPa) were analyzed by three-way repeated measures ANOVA and post-hoc Tukey test (α= 5%). Analysis were performed for each substrate separately. On sound dentin, the etching strategy did not influence bond strength of universal adhesives and no significant statistical differences were found for bond strength values after 6 months of water storage. On caries-affected dentin, adhesive systems also showed similar results regardless etching strategies. However, significant reduction in bond strength values was found after six months. The etching strategy did not influence bond strength performance of universal adhesives on dentin substrate, although the long-term bond strength is decreased on caries-affected dentin.